Pengaruh Sistem Pemasaran Hasil Pertanian dan Keterbatasan Penjualan Terhadap Perekonomian Petani - Prastiwi, Julia E (Jurnal EMT KITA, 2024)
This research discusses the influence of marketing and sales strategies on the economy of farmers in Bayem Village, Kasembon District, Malang Regency. This research aims to determine the impact of the agricultural product marketing system on the farmer's economy in Bayem Village, as well as to evaluate the influence of the agricultural product marketing system and sales limitations on the farmer's economy in Bayem Village. The sampling technique used a simple random sampling method with a total sample of 35 farmers in Bayem Village. The data analysis technique used is multiple linear regression analysis. The research results show that marketing strategies have a significant effect on the farmer's economy. This can be seen from the calculation results for the t variable for Marketing Strategy (X1) of 2,933 with a significance value (sig.) or partial p-value of 0.006, which is smaller than 0.05. Therefore, Marketing Strategy (X1) taking into account other variables has a partially significant influence on the dependent, namely the Farmer's Economy (Y). Furthermore, sales also have a significant effect on the farmer's economy, with a t value of the X2 variable of 3.076 and a significance value of 0.004, which is also less than 0.05. This shows that X2 has a significant influence on the dependent variable, namely Y. Overall, marketing and sales strategies together have a significant influence on the farmer's economy. This is confirmed by the calculation results in the Anova F Test of 17,124 with an F test significance (Sig) of 0.000, which is less than 0.05. Therefore, it can be concluded that there is a simultaneous influence of the independent variable on the dependent variable so that H0 is rejected and H1 is accepted.